Dynamic etching of soluble surface layers with on-line inductively coupled plasma mass spectrometry detection – a novel approach for determination of complex metal oxide surface cation stoichiometry. Issue 8 (7th July 2016) - Limbeck, Andreas; Rupp, Ghislain M.; Kubicek, Markus; Téllez, Helena; Druce, John; Ishihara, Tatsumi; Kilner, John A.; Fleig, Jürgen
Abstract : In this work, an innovative approach for determining the surface stoichiometry of complex metal oxide (CMO) thin films is presented. Abstract : In this work, an innovative approach for determining the surface stoichiometry of complex metal oxide (CMO) thin films is presented. The procedure is based on treatment of the sample surface with different etching solutions, followed by on-line analysis of the derived eluates using inductively coupled plasma – mass spectrometry (ICP-MS). Via consecutive treatment of the sample surface with water and diluted HCl, a differentiation between water soluble and acid soluble parts of near surface regions in thin films is enabled. The developed procedure was applied for the analysis of dense La0.6 Sr0.4 CoO3− δ (LSC) thin films indicating the presence of a water soluble Sr-rich phase with sub nm-thickness on top of the LSC films. The step-wise optimization of this technique is reported and the results are compared to measurements performed by low-energy ion scattering (LEIS). The detrimental effect of the water soluble Sr rich phase on the oxygen exchange activity of LSC thin film electrodes is verified by electrochemical impedance spectroscopy (EIS).